Amyloid β fibrils disruption by kolaviron: Molecular docking and extended molecular dynamics simulation studies. (October 2021) - Adewole, Kayode Ezekiel; Gyebi, Gideon A.; Ibrahim, Ibrahim M.
Graphical abstract: Highlights: Comprehensive in silico docking and molecular dynamics were used to mimic kolaviron/amyloid-beta fibrils (Aβ) system. Kolaviron moved within the Aβ fibrils and destabilized the preformed Aβ fibrils. Thus, kolaviron is a potential anti-amyloidogenic compound and may be relevant in the treatment of Alzheimer's disease. Abstract: Garcinia kola (GK) produces notable effects against neurodegenerative conditions, including experimentally-induced Alzheimer's disease (AD). These remarkable effects are basically attributable to kolaviron (KV), a bioflavonoid constituent of this seed. Specifically, it has been reported that in AD models, KV produces interesting neuroprotective effects, being able to diminish associated neurotoxicity, via modulation of antioxidative, inflammatory and other disease modifying processes. Intriguingly, the effect of KV on amyloid-beta (Aβ) aggregation and disruption of preformed Aβ fibrils have not been studied. In this study, we have described a thorough computational study on the mechanism of action of KV as an Aβ fibrils disruptor at molecular level. We used comprehensive in silico docking evaluations and extended molecular dynamics simulation to mimic KV/Aβ fibrils system. Results indicate that KV was able to move within the Aβ fibrils, binding with important residues and components in the Aβ peptide identified to be vital for stabilizing preformed fibrils. KV destabilized the assembled Aβ fibrils, indicating the ability KV as a potential anti-amyloidogenic agent. Furthermore, this work highlighted the possibility of identifying new multifunctional phytocompounds as potent AD drugs.